Accentuated Eccentric Loading in the Bench Press: Considerations for Eccentric and Concentric Loading - Christopher B. Taber; Jared R. Morris; John P. Wagle; Justin J. Merrigan (MDPI AG, 2021)
This study examined the effects of accentuated eccentric loading (AEL) on bench press velocities across a spectrum of concentric and eccentric loads. Ten strength trained men (bench press one-repetition maximum (1-RM): 124.3 ± 19.4 kg; relative strength ratio: 1.5 ± 0.2 kg∙body mass−1) participated. Subjects completed bench press repetitions using concentric loads from 30% to 80% 1-RM in 10% increments in each experimental session. The AEL protocols were implemented using 100% (AEL100) and 110% 1-RM (AEL110) loads during the eccentric action, while the eccentric load remained the same as the concentric for traditional loading (TRAD). Multilevel models analyzed the effects of each AEL protocol on concentric velocities across concentric loads (p < 0.05). Faster concentric velocities were observed at 30% 1-RM and 80% 1-RM with AEL100 compared to TRAD (p ≤ 0.05) but this effect was reduced for individuals moving the barbell through a greater displacement. Additionally, AEL110 presented a greater change in velocity from 30% to 80% 1-RM than TRAD (p ≤ 0.05). The AEL100 protocol resulted in faster concentric velocities throughout concentric loads of 30-80% 1-RM, but AEL110 may have been too great to elicit consistent performance enhancements. Thus, the efficacy of AEL at various concentric loads is dependent on the eccentric loading and barbell displacement.